Personality-intelligence interface : the relationship between conscientiousness and intelligence - Grant, Sarah (My University, 2006)
The aim of this study was to investigate the relationship between conscientiousness and intelligence. Specifically, this study intended to replicate a previous study by Moutafi et. al. (2004) that found conscientiousness to be negatively correlated with intelligence (Moutafi, Furnham, & Paltiel, 2004). It was proposed that this negative relationship could be explained by the theory of compensation, which hypothesized that individuals low on fluid intelligence could compensate for this intellectual disadvantage by developing higher levels of the personality trait conscientiousness (Moutafi, et. al., 2004). However, a number of other theories regarding the Personality-Intelligence Interface would not predict a negative relationship between conscientiousness and intelligence. To examine the relationship between conscientiousness and intelligence, fifty participants were tested on both fluid (using Raven’s Progressive Matrices and an inspection time task) and crystallized intelligence (using Wechsler’s Test of Adult Reading). Participants completed a personality questionnaire that included sixty items designed specifically to assess the six facets of conscientiousness (self-efficacy, orderliness, dutifulness, achievement-striving, self-discipline and cautiousness). Using a one-tailed Pearson’s Product-Moment correlation, neither conscientiousness nor any of its six facets were found to correlate with any of the intelligence measures. Furthermore, the well replicated correlations between openness and intelligence; and neuroticism and intelligence were not found either. Despite a number of limitations concerning the nature of the sample used, failing to replicate the negative relationship between conscientiousness and intelligence raises fundamental questions regarding the applicability of the theory of compensation. This led to the conclusion that more research is needed, using well-validated measures, to assess whether a relationship exists between conscientiousness and intelligence and what this may be.
Keywords: personality-intelligence interface; conscientiousness; intelligence; fluid intelligence; inspection time; crystallized intelligence; Pearson's Product-Moment correlation